Mock target IR thermography for indoor air temperature measurement - Fokaides, Paris A.; Jurelionis, Andrius; Gagyte, Laura; Kalogirou, Soteris A. (My University, 2016)
The aim of this study is the proof of concept and the validation in laboratory environment of a novel technique for in-situ measurement of indoor air temperature using IR thermography, the mock target IR thermography. The technique is based on the use of mock targets with appropriate hygrothermal properties. The physics of the examined concept are introduced by employing analytical predictions and numerical analysis, using finite elements simulations (Comsol Multiphysics). The selection of the mock target material is also justified and the optimal solutions are discussed. The laboratory validation of the proposed technique was implemented under controlled conditions in the climate chamber of the Kaunas University of Technology (Lithuania). The concept was tested under different indoor conditions and with the use of various mock targets. The measurements were also validated with the use of a compatible measurement technique (thermocouples). The prerequisites for the implementation of the technique, as well as the conditions under which the proposed technique provides reliable results are presented.
Keywords: Climate chamber; Finite Element Method; Indoor air temperature; IR thermography; Numerical analysis; Proof of concept